Structural Study of a New HIV‐1 Entry Inhibitor and Interaction with the HIV‐1 Fusion Peptide in Dodecylphosphocholine Micelles. Issue 48 (3rd August 2017) - Pérez, Yolanda; Gómara, Maria José; Yuste, Eloísa; Gómez‐Gutierrez, Patricia; Pérez, Juan Jesús; Haro, Isabel
Abstract: Previous studies support the hypothesis that the envelope GB virus C (GBV‐C) E1 protein interferes the HIV‐1 entry and that a peptide, derived from the region 139–156 of this protein, has been defined as a novel HIV‐1 entry inhibitor. In this work, we firstly focus on the characterization of the structural features of this peptide, which are determinant for its anti‐HIV‐1 activity and secondly, on the study of its interaction with the proposed viral target (i.e., the HIV‐1 fusion peptide). We report the structure of the peptide determined by NMR spectroscopy in dodecylphosphocholine (DPC) micelles solved by using restrained molecular dynamics calculations. The acquisition of different NMR experiments in DPC micelles (i.e., peptide–peptide titration, diffusion NMR spectroscopy, and addition of paramagnetic relaxation agents) allows a proposal of an inhibition mechanism. We conclude that a 18‐mer peptide from the non‐pathogenic E1 GBV‐C protein, with a helix–turn–helix structure inhibits HIV‐1 by binding to the HIV‐1 fusion peptide at the membrane level, thereby interfering with those domains in the HIV‐1, which are critical for stabilizing the six‐helix bundle formation in a membranous environment. Abstract : No admittance ! The peptide E1P47 forms a helix–turn–helix motif in zwitterionic dodecylphosphocholine (DPC) micelles, a structure, which is relevant for its inhibitory activity. E1P47 interacts with the HIV‐1 fusion peptide at the membrane level by interfering with those domains in the HIV‐1, which are critical for stabilizing the six‐helix bundle formation in a membranous environment (see figure).